Raso Photography Studio / Raja Sofiya Raja Kamaruddin - Raja Kamaruddin, Raja Sofiya (2020)
Overview of this business plan. The first thing is about the introduction of this business plan that people should know. The business is about a photography service in a rural area. This business plan also has been a proof that in a rural area we can build a successful business because the number of population in this location is high. Moreover, in this business plan too, we has explained about the uniqueness of our company and what makes our company different from others. Our company has its own identity because the name of the company itself has brought something meaningful towards other people.